2016
DOI: 10.1111/jeb.12827
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of the little fire ant Wasmannia auropunctata before global invasion: inferring dispersal patterns, niche requirements and past and present distribution within its native range

Abstract: The evolutionary history of invasive species within their native range may involve key processes that allow them to colonize new habitats. Therefore, phylogeographic studies of invasive species within their native ranges are useful to understand invasion biology in an evolutionary context. Here we integrated classical and Bayesian phylogeographic methods using mitochondrial and nuclear DNA markers with a palaeodistribution modelling approach, to infer the phylogeographic history of the invasive ant Wasmannia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 111 publications
(133 reference statements)
1
13
0
Order By: Relevance
“…In areas partially overlapping with the one identified in this work, the possible occurrence of a secondary contact between highly divergent clades has been reported for the Rufous-collared sparrow [ 48 ] and the little fire ant [ 49 ]. In addition, [ 50 ] suggested the co-existence of multiple cryptic species among 18 species of butterflies inhabiting this area, similar to what we found in a previous work for lineages I and II of N .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In areas partially overlapping with the one identified in this work, the possible occurrence of a secondary contact between highly divergent clades has been reported for the Rufous-collared sparrow [ 48 ] and the little fire ant [ 49 ]. In addition, [ 50 ] suggested the co-existence of multiple cryptic species among 18 species of butterflies inhabiting this area, similar to what we found in a previous work for lineages I and II of N .…”
Section: Discussionsupporting
confidence: 51%
“…Lineages in suture zones diverging due to isolation in Pleistocene refugia were suggested to have concomitant expansion times rather than divergence times, these expansions having been taken place in early to mid-Holocene times [ 55 ], as is the case for N . cervinus [ 21 ] and the little fire ant [ 49 ]. This assumption provides some additional support for the existence of a suture zone in the area under consideration.…”
Section: Discussionmentioning
confidence: 99%
“…There is an emerging willingness to integrate genetic, experimental, and modeling approaches in understanding invasions. Some studies have combined genetic identification of source populations with niche shift models (e.g., Chefaoui & Varela‐Álvarez, ; Chifflet et al., ; Fitzpatrick, Weltzin, Sanders, & Dunn, ; Ikeda et al., ) or with estimates of phenotypic shifts (e.g., Agrawal et al., ; Bossdorf et al., ; Schrieber et al., ). Others have combined tests of phenotypic shifts with niche models (e.g., Dlugosch et al., ; Turner, Fréville, & Rieseberg, ; Wittmann, Barnes, Jerde, Jones, & Lodge, ), but more rarely are all three approaches used simultaneously (but see Rey et al., ; Hill, Chown, & Hoffmann, ).…”
Section: Discussionmentioning
confidence: 99%
“…While there is an ongoing debate around the evolutionary impacts of the habitat fragmentations caused by Pleistocene glaciations in the Brazilian Atlantic Forest, much less is known about the past status of this forest in Argentina. However, it was recently suggested that the Atlantic Forest in Misiones was a refuge during the Last Glacial Maximum for the fire ant Wasmannia auropunctata [ 71 ]. As well, two new forest refugia in Paraná and Santa Catarina, two Brazilian states bordering Misiones, have been recently proposed [ 69 ].…”
Section: Discussionmentioning
confidence: 99%